DARI PEMERINTAHAN DESA KEMBALI KE PEMERINTAHAN NAGARI: STUDI KASUS NAGARI AUA KUNIANG KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT TAHUN 1983-2012 - Yani, Patra; Nurhuda, Ahmad; Meldawati, Meldawati (Pendidikan Sejarah, 2014)
The main issue in this study is the change in system administration Nagari Aua Kuniang since validity UU No. 5 of 1979 in Sumatera Barat and outlines the proces of the system of government Chang to government Nagari village in 2001 with the No. 22 of 1999 on Regional Autonomy . But in this Paper discussed until in 2012 because this year Nagari Aua Kuniang has managed to become a good Nagari and each device Nagari has been carrying out its obligations in accordance with their respective duties . The purpose of this study is to describe the structure of the form, function of the lowest government system, to see the shape of the system changes back to the system administration Nagari, as well as to look after the implementation of the government back to the Nagari.The study used the historical method which includes four stages include Heuristic, Critic, interpretation, and Historiography. First, heuristic are searching for and collecting data through primary and secondary sources were found through written sources and interviews. Second, the source of critic is to do research on data collected through internal and external critic is whether the data is the correct data and in accordance with the needs of research. Third, the data interpretation is activity undertaken to interpret the facts. Fourth, Historiography is stringing research results in the form of scientific papers (Thesis).The results showed that , with the change of government system to Nagari village has brought changes to the lives of village Aua Kuniang. Such changes can be seen both in government agencies, indigenous organizations, and social institutions. The implementation of village government system so that the underlying desire to return to the system of government in 2001 in Kenagarian Aua Kuniang constituted with the issuance of UU No.22 of 1999 on regional autonomy, the law has provided an opportunity for the region to progress the region. Implementation of the government after returning to Nagari in Aua Kuniang begins with the establishment of institutions that support the governmentÂ  Nagari, including the executive (Wali Nagari), legislative (DPN), and judicative (KAN).